Description of a new species of Prolytta Kaszab, 1959, from Tanzania (Coleoptera, Meloidae) - François, Mickaël (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Prolytta nyassica spec. nov. is described from Tanzania. A new species-group is established for this species. A picture of the habitus and labels, a drawing of aedeagus and a map of distribution are provided. Nomenclatural acts Prolytta nyassica spec. nov. – urn:lsid:zoobank.org:act:36F49FF7-D23D-4536-8B28-28E82865374B